Early outcome of management of Bladder Carcinoma in Octogenarian at Tertiary care hospital - Thapa, Narayan; Thapa, Bikash Bahadur; Basukala, Sunil; Bhandari, Bharat Bahadur; Phuyal, Anjit (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Urothelial bladder cancer is a cancer of environment and age, and its incidence increases with age peaking in the 80s. Unlike in other malignancies in which cancer tends to be aggressive in young individuals, the probability of developing muscle invasive bladder cancer increases with age. The standard treatment for non-metastatic muscle invasive bladder cancer is radical cystectomy. However, there is controversy regarding the outcome of radical cystectomy in elderly patients, especially more than 80 years. Methods: This is a retrospective study of prospectively collected data. All patients > 80 years of age with bladder carcinoma were included in the study. A patient with good functional status was offered Radical Cystectomy. Patients not fit for surgery or refusing surgery were managed with TURBT. Results: A total of 23 patients were included in the study. Out of which, 13 patients underwent radical cystectomy (RC) with ileal conduit and while ten patients who refused surgery were managed with TURBT and chemotherapy. The prognosis of patients with MIBC managed with TURBT was within 1 year. While patients who have undergone RC had survived more than 1 year. Conclusions: Radical Cystectomy is a safe, feasible, and effective treatment option for the carefully selected octogenarian. Age is just a number and should not be an absolute contraindication for radical cystectomy in patients with non-metastatic muscle invasive bladder cancer.